IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL DENGAN PENGUATAN PROFIL PELAJAR PANCASILA DIMENSI GOTONG ROYONG DI KELAS VB SD NEGERI KAUMAN 1 - Asfari Mahiruddin Asmi; Candra Utama; Elly Fithriyanasari; Asfari Mahiruddin Asmi; Candra Utama (Universitas Negeri Malang, 2024)
This research was conducted to see the application of contextual learning with the strengthening of the gotong royong dimension in the Pancasila Student Profile. The applied material is the utilization of biodiversity biodiversity utilization. The method used was descriptive qualitative. Data obtained from learning outcomes, observer responses, learner questionnaires, and researcher observations as a model teacher. as a model teacher. This lesson was conducted in class VB with the number of students learners 28 and those present at the time of implementation were 23 people. Research results The results showed that contextual learning with the reinforcement of the gotong royong dimension was successfully carried out and can provide dimension was successfully carried out and could provide real understanding to students, as well as build character in collaborating with students. learners, as well as building character in collaboration, caring, sharing as the goal of the gotong royong dimension. the purpose of the gotong royong dimension in the Pancasila Student Profile.